Crime and punishment: An examination of school context and student characteristics that predict out-of-school suspension. (December 2018) - Cruz, Rebecca A.; Rodl, Janelle E.
Abstract: Exclusionary discipline can have long-term adverse effects on both students and schools. The purpose of this study was to investigate student demographic, school context, and school practice factors that are predictors of out-of-school suspension in one school district to determine if there were disparities across demographic groups over time. The sample consisted of archival data from 2010 to 2016 for approximately 56, 000 students in 41 schools in a diverse school district in California. This study examined students' suspension risk over time using a multilevel model. Results confirmed that student-level predictors such as gender, race, and grade level were consistent predictors of suspension, and that school context factors such as suspension rate impacted risk. Results indicated that school practices meant to reduce suspensions were not necessarily ameliorative across time for most demographic groups, but some school practices that academically engage students at a young age may be more impactful at reducing suspension risk over time. These results affirm the importance of school-level factors, as well as a combination of practices that seek to change school culture with regard to reducing exclusionary discipline. Highlights: School practices meant to reduce suspensions are not necessarily ameliorative across time for most demographic groups. Some school practices that academically engage students at a young age may be more impactful at reducing suspension risk. School-level variables often produce a "frog pond" effect in which student behavior is judged relative to peers. Underlying theories of action related to suspension reduction programs may not align well with root causes of disparities.